2019
DOI: 10.1007/s10549-019-05385-8
|View full text |Cite
|
Sign up to set email alerts
|

Marital status is an independent prognostic factor in inflammatory breast cancer patients: an analysis of the surveillance, epidemiology, and end results database

Abstract: ObjectivesThe aim of this analysis was to study the impact of marital status on inflammatory breast cancer (IBC) patients, as the prognostic impact is yet to be studied in detail.MethodsData of IBC patients from 2004 to 2010 were sorted out from the database of surveillance, epidemiology, and end results (SEER), and overall survival (OS) rates and breast cancer-specific survival (CSS) rates were compared between a group of married and unmarried patients. The comparison was performed by Kaplan–Meier method with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
(32 reference statements)
5
35
1
Order By: Relevance
“…For clinicians, more care should be taken when applying RTCT in tumors sized <2 cm. Additionally, after adjusting for several factors, we found that divorced, separated, or widowed women had worse OS than married women, which confirms the benefits of marriage on survival found by previous studies regarding vulvar, ovarian, endometrial, and breast cancers (32)(33)(34)(35). The most likely reason for the survival benefit from marriage is that divorced, separated, or widowed patients have worse adherence to prescribed treatments than married patients.…”
Section: Discussionsupporting
confidence: 87%
“…For clinicians, more care should be taken when applying RTCT in tumors sized <2 cm. Additionally, after adjusting for several factors, we found that divorced, separated, or widowed women had worse OS than married women, which confirms the benefits of marriage on survival found by previous studies regarding vulvar, ovarian, endometrial, and breast cancers (32)(33)(34)(35). The most likely reason for the survival benefit from marriage is that divorced, separated, or widowed patients have worse adherence to prescribed treatments than married patients.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Zhou et al proved that marital status was an independent prognostic risk factor for patients with pancreatic endocrine cancer 18 . Similar findings have also been discovered in breast cancer and nasopharyngeal carcinoma 15,29 . The above researches all exhibited that the prognosis of married patients is remarkably better than that of unmarried ones.…”
Section: Discussionsupporting
confidence: 86%
“…Current data suggest that more single women received an initial diagnosis with breast cancer in the ED than married women. This finding agrees with the literature that single women had a delay to diagnosis and worse prognosis more often than married women [ 8 , 18 - 20 ]. This observation can be attributed to the fact that single women are more likely to lack social and financial support regarding medical issues.…”
Section: Discussionsupporting
confidence: 93%